Association between maternal polycystic ovary syndrome and attention-deficit/hyperactivity disorder in offspring aged 3–6 years: A Chinese population-based study - Zhang, Yuying; Lu, Dali; Guo, Vivian Yawei; Wang, Yuqing; Qiu, Shuangyan; Zhang, Jingyu; Zhang, Yan; Chen, Weiqing; Wang, Baoping; Yang, Weikang (Frontiers in Public Health, 2023)
Background Maternal polycystic ovary syndrome (PCOS) may increase the risk of attention-deficit/hyperactivity disorder (ADHD) in offspring; however, their association remains unexplored in Asian populations. Hence, this study aimed to investigate the association between maternal PCOS and ADHD in offspring aged 3–6 years and whether it differed by offspring sex. Methods This was a district-wide population-based study of 87,081 preschoolers from 234 kindergartens in Longhua District, Shenzhen, China. The parents were invited to complete a self-administrated questionnaire covering information on socio-demographics, maternal disease history, and child behavior. ADHD symptoms were measured with the parent-rating 26-item Swanson, Nolan, and Pelham Rating Scale (SNAP-IV). Logistic regression was performed to examine the associations between maternal PCOS and ADHD symptoms in offspring. Results The response rate was 80% and 63,390 mother-child pairs were included. Of the mothers, 1,667 (2.6%) reported PCOS diagnoses. The mean age of children at ADHD assessment was 4.86 ± 0.84[SD] years, and 53.6% were boys. Children with maternal PCOS had a higher risk of developing ADHD symptoms than other children (12.0 vs. 9.4%, adjusted odds ratio [OR] = 1.32, 95% CI: 1.13–1.54). The risk estimate was significant in boys (adjusted OR = 1.38, 95% CI: 1.14–1.66) but not in girls (adjusted OR = 1.23, 95% CI: 0.94–1.57, P for interaction = 0.391). Treatment of PCOS tended to be associated with a lower risk of ADHD symptoms than untreated PCOS albeit risk confidence intervals were overlapped (treated: adjusted OR = 1.28, 95% CI: 1.06–1.54 vs. untreated: adjusted OR = 1.14, 95% CI: 1.08–1.83). Conclusion Maternal PCOS increases the risk of developing ADHD in offspring, especially boys. Further studies are warranted to confirm our findings, and early neurodevelopmental screening may be needed in children born to mothers with PCOS.